2019
DOI: 10.1002/ajpa.23785
|View full text |Cite
|
Sign up to set email alerts
|

Diagnodent and VistaCam may be unsuitable for the evaluation of dental caries in archeological teeth

Abstract: Objectives: The aim of the study was to compare the usefulness of fluorescence-based caries detection systems (Diagnodent and VistaCam) for the assessment of carious lesions on archeological molars. Materials and methods: The study material consisted of teeth from the Cemetery of St. Mary Magdalene (Cmentarz sw. Marii Magdaleny) in Wrocław, Poland. A sample of 178 permanent molars from 38 skulls were examined. Five surfaces of teeth (occlusal, mesial, distal, buccal, and lingual) were assessed on either basica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
2
3
0
1
Order By: Relevance
“…This result is in dis-agreement with Dąbrowski et al (2019) who found the area under curve (AUC) for vista cam was 54.2; however, this result may be due to the different structure of the archaeological teeth examined in this study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result is in dis-agreement with Dąbrowski et al (2019) who found the area under curve (AUC) for vista cam was 54.2; however, this result may be due to the different structure of the archaeological teeth examined in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Many researches also confirmed the high level of reproducibility of the camera likewise confirmed in studies by Rodrigues et al (2008), Jablonski-Momeni et al (2011), Novaes, et al (2012) and De Benedetto et al (2011). This finding was in dis-agreement with Dąbrowski et al (2019) who found that the interobserver weighted kappa value for VistaCam was 0.54, and this result is considered far from being satisfactory. This result may be due to the different biogenic apatite of the archaeological teeth examined in this study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The values of the AUC (the area under the ROC curve) make a comparison of predictive models possible. A “fair model” is one where the AUC is 70–75% (Dąbrowski et al, 2019). In the case of individual angular notch measurements, such values can be observed for two measurements: the length of side AB, which is also the notch length, and the length of side AC (the front side of the notch).…”
Section: Discussionmentioning
confidence: 99%
“…An additional evaluation parameter is the Area Under Curve (AUC) of the ROC. This is a measure of the accuracy of a given model: the higher the AUC value, the better the model (Dąbrowski et al, 2019). An AUC at a level of 70–75% is characteristic of “fair predictors.” On the basis of the different AUC values, the predictive value of the compared characteristics can be compared.…”
Section: Methodsmentioning
confidence: 99%